Ownership of Cultural Goods - Halonen-Akatwijuka, Maija; Pafilis, Evagelos (University of Bristol, 2017)
We examine the return of cultural goods to their home country. The cultural good can be unified or separated into two countries. We show that nonintegration and separation of the cultural good is initially optimal when the host invests in the restoration of the cultural good and his unique restoration skill makes him an indispensable trading partner. The return of the cultural good to its home country and shift of ownership becomes optimal when the restoration stage is over and the host’s investment changes to human capital, which reduces the spillover from his investment, and technological changes make him a relatively dispensable trading partner. Alternatively, the cultural good can be returned due to changes in the valuation of the cultural good. The return can be triggered when unification is efficient but it is possible that the return is triggered even when separation is efficient.
Keywords: public goods; cultural goods; property rights; location